Teaching of Language Skills to Students with Autism Spectrum Disorder during the COVID-19 Pandemic - Ngo, Cristy Grace A.; Duhaylungsod, Nikka L.; Sacatan, Norhania B. (CV. Tripe Konsultan, 2024)
This phenomenological study aimed to describe the teaching experiences, coping mechanisms, insights, and new teaching techniques of teachers in teaching language skills to students with Autism Spectrum Disorder (ASD) amidst pandemic. This study used a qualitative research design and the Colaizzi analysis strategy in analyzing the results. The five licensed Special Education teachers in both elementary and high school levels were selected through purposive sampling. The researchers constructed an interview guide and conducted semi-structured in-depth interviews. Findings and analyses of the study showed that the sudden shift of the programs and the intensified difficulty in getting the attention of the students with ASD were the challenges these teachers experienced. Consequently, the teachers motivated themselves to continue teaching, but sometimes the support from various support systems was inadequate. Further, they adapted a medical strategy and modified some traditional techniques to ensure the effectiveness of the instruction. The teachers can take advantage of the impairments with their teaching techniques.